(untitled) (CAHIERS MAGELLANES-NS, 2024)
Conflict is an inevitable aspect of human interaction, particularly in organizational settings. This paper explores the influence of gender on the conflict management styles adopted by managers within organizations. Drawing on Rahim's Organizational Conflict Inventory-II (ROCI-II) and existing literature, the study investigates the conflict handling behaviors of male and female managers in select banking organizations. The results indicate that while both male and female managers prefer integrating conflict management style, they differ in their preferences for avoiding and compromising styles. Female managers exhibit a higher preference for avoiding conflict, possibly influenced by cultural factors and underrepresentation in managerial roles. The findings underscore the importance of fostering conflict management skills among employees to promote teamwork, trust, and innovation within organizations. Future research should delve into the sources of conflict and consider the influence of personality and culture on conflict handling behaviors.